Community Protection with Local Wisdom?: Generational Communication Gap between Mamak and Kamanakan in Facing the Covid-19 Pandemic - Emeraldy Chatra; Ilham Havifi (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
This research is an attempt to understand communication and local wisdom centered on mamak (MmK) and kamanakan (KmN) communication in the Minangkabau community in West Sumatra in tackling the Covid-19 pandemic. The research is motivated by the reality of the world which is experiencing a crisis due to the Covid-19 pandemic, which has caused many setbacks in all fields, especially in the social, cultural and economic fields. Data analysis was carried out by exploring and narrating community experiences, and analyzing domains that are considered potential for developing cultural communication, maintaining local wisdom and communication gaps between generations. The results of the study show that the MmK – KmN communication is still quite well maintained and useful for the educational process and solving problems that arise as a result of the Covid-19 pandemic. However, the vertical communication pattern from top to bottom places MMK as the party that knows best about the problem of communication generations gaps, so it must be modified according to the development of KmN's knowledge which is more technologically literate and has more access to various sources of information.